Disruption of the HLA-E/NKG2X axis is associated with uncontrolled HIV infections - Romero-Martín, Luis; Duran-Castells, Clara; Olivella, Mireia; Rosás-Umbert, Míriam; Ruiz-Riol, Marta; Sanchez, Jorge; Hartigan-O´Connor, Dennis; Mothe, Beatriz; Olvera, Àlex; Brander, Christian (Frontiers in Immunology, 2022)
The contribution of the HLA-E/NKG2X axis in NK-mediated control of HIV infection remains unclear. We have studied the relationship between HLA-E expression and phenotypical as well as functional characteristics of NK cells, in the context of chronic HIV infection and in an in vitro model of acute infection. High viremia in HIV+ individuals was related to increased HLA-E expression, changes in NK subpopulations, specially a reduction of the CD56bright as well as an increase in adaptive NK subpopulation, a reversion of the NKG2A/NKG2C expression ratio and a loss of positive and negative regulation of NK mediated by HLA-E. This was reflected in a lower cytotoxic, degranulation and cytokine production capacity, especially in CD56bright and adaptive NK. In line with these results, HLA-E expression showed a positive correlation with viral growth inhibition at 7 days in an in vitro model of acute infection, that was lost after 14 days culture. We determined that only one out of 11 described HIV-derived HLA-E epitopes increased HLA-E surface stability. In spite of that 8 were capable of increasing degranulation and 3 drove differences in NK-cell mediated cell lysis or cytokine secretion. In conclusion, our results indicate that HLA-E presenting HIV-derived epitopes may sensitize target cells for NK lysis in early infection, whereas prolonged exposure to elevated HLA-E expression levels may lead to NK dysfunction and reduced viral control.